Rapid Reconfiguration of the Greenland Ice Sheet Coastal Margin. Issue 11 (3rd November 2020) - Moon, Twila A.; Gardner, Alex S.; Csatho, Beata; Parmuzin, Ivan; Fahnestock, Mark A.
Abstract: The Greenland Ice Sheet has lost mass at an accelerating rate over the last two decades, but limits of early remote sensing restricted examination of localized change at an ice‐sheet‐wide scale. We use satellite‐derived ice sheet surface velocities, glacier terminus advance/retreat, and surface elevation change data spanning 1985–2015 to explore local characteristics of what is now a rapid reconfiguration of the ice sheet coastal margin. Widespread glacier terminus retreat is a more consistent climate response indicator than surface velocities, though local velocity patterns provide indicators of ice flow reconfiguration, including narrowing zones of fast‐flow, ice flow rerouting, and outlet abandonment. The implications of this observed rapid reconfiguration are wide ranging and likely include alteration of subglacial hydrology, iceberg discharge, liquid freshwater flux, potential nutrient and sediment flux, and mass flux. Without detailed observations of earlier deglaciations and with present limits on ice sheet model capabilities, these observational records provide an important analogue for past deglaciation and for projecting future ice loss. Plain Language Summary: From the 1970s through the early 1990s, the Greenland Ice Sheet was roughly in balance, with mass gains equaling mass losses. In the mid‐1990s, however, Greenland ice loss began and accelerated. By combining 1985–2015 records of changing outlet glacier flow, ice edge positions, and ice sheet surface elevation, we show that the margin of the Greenland Ice Sheet is undergoing a significant reconfiguration. Ice edge retreat is ubiquitous, with virtually no glaciers experiencing advance, while some areas of the ice sheet have sped up and others have slowed. Our observations reveal a rapid reconfiguration around the full ice sheet margin, with narrowing areas of fast ice flow, changes in the routing of ice flow, and glacier outlets that are likely being abandoned. The implications of rapid ice sheet reconfiguration are wide ranging. Water movement underneath the ice sheet likely changes, along with the quantity and timing of iceberg production and freshwater input to the ocean, affecting the nutrients and sediment transport from the ice sheet to local and regional ecosystems. Without detailed observations of earlier deglaciations and with limits on ice sheet computer simulation capabilities, these observational records provide an important analogue for past deglaciation and for projecting future ice loss. Key Points: Ice sheet surface velocity and ice edge records since the mid‐1980s show rapid ice sheet reconfiguration during the 21st century Despite widespread retreat, glaciers sped up and slowed down, revealing upstream links and strong topographic control of ice sheet behavior Reconfiguration on decadal timescales includes flow rerouting, narrowing of fast flow zones, and likely outlet abandonment